Digital Adoption Asistance for the Wood Craftmans Community Towards Upgrading MSMEs: Pendampingan Adopsi Digital Bagi Komunitas Pengrajin Kayu Menuju UMKM Naik Kelas - Cynthia, Eka Pandu; Afriyanti, Liza; Arifandy, M. Imam (Universitas Lancang Kuning, 2024)
The government has launched the MSME Level Up program, which is a government program to facilitate MSMEs to move up a class in terms of digital adoption in order to expand marketing access, and business efficiency, increase sales transactions, and increase the competitiveness of MSMEs. Pekanbaru City has 1,034 registered MSMEs that are engaged in producing various products from wood. This PKM activity has succeeded in providing education and assistance to MSME Furniqa and MSME KadoKekayuan partners regarding Digital Adoption, Basics of Digital Media, Creating Digital Content, Digital Benchmarking, Advertising on Google and Meta (Instagram, Facebook, Tiktok), Maximizing Digital Marketing (Digital Simulation Marketing Templates), Getting to Know Analytics (Google and Meta), Measuring the Effectiveness of Advertising Campaigns, and Optimizing Search Engine Optimization (SEO) through content. As an evaluation, the level of success of activities and understanding of partners has been measured by obtaining results >80%.